The influence of “mild” stress on biochemical markers of pathology in the liver of rats - Velychko, V. (Journal of Education, Health and Sport, 2025)
Background. It is known that stress negatively affects the liver. Under the influence of stress factors, oxidative stress occurs in the liver, which is the main pathogenetic mechanism of hepatitis development. In the process of post-stress reactions, other pathogenetic processes are also activated, due to the activation of hydrolytic processes, increased permeability of histo-hematic and intestinal barriers. Aim. To investigate the effect of stress on the condition of the liver. Methods. Rats were stressed by holding the animals at −20 °C for 5 minutes (“mild” stress). 5 and 24 hours after stress, proteolysis activity (substrate casein, pH 7,6; substrate albumin, pH 5,5) was determined in the liver by the Kunitz method, BAEE esterase activity by the spectrophotometric method, and oxidative status by the rate of ascorbic acid oxidation. Results. After 24 hours, a decrease in proteolysis activity is observed (substrate casein, pH 7,6) and after 5 hours the level of peroxidation decreases. Albumin proteolysis activity (pH 5,5) does not change. There is a tendency to increase BAEE-esterase activity. Conclusion. A decrease in the level of proteolysis and oxidation may indicate a positive effect of “mild” stress on the condition of the liver.